Critical success factor of ISO 9001 Quality Management Certification Implementation among small and medium enterprise in Malaysia - Zainudin, Dolhadi; Zainuddin, Yusserie (International Institute of Social and Economic Sciences (IISES), 2013)
The study attempts to predict the relationship between critical success factors (CSFs) and adoption of ISO 9000 and to identify which CSFs play the main role in achieving ISO 9000 standard. A survey using structured questionnaire was employed. A total of 155 respondents from 970 small and medium enterprises participated in this study. 619